Size, shape, and dose — three crucial determinants for applying nanoparticles in sustainable plant biology - Anindita Dey; Papiya Nandy (Academia Biology)
Nanoparticles (NPs) are easily accessed in biological systems due to their widespread distribution, and they may have neutral, promoting, or inhibiting effects. The positive impact on plants is shown in better plant growth, increased biomass production, enhanced enzyme actions, and improved crop productivity. In contrast, negative effects include germination retardation, growth inhibition, cell impairment, deterioration, and eventually death. Different outcomes depend on factors such as plant species, the physicochemical nature of the NP, NP size, shape, and concentration, and the type of medium. More research is needed on many fronts regarding the interaction of NPs with plants, including the absorption capacity of diverse plant species, methods of uptake and translocation, and interactions between the NPs and plant tissues at cellular and genetic levels. However, the effects of these tiny particles after entering the plant body will be influenced directly or indirectly by the three most critical factors: the shape, size, and dose of NPs used during applications. Therefore, analyzing the outcomes of these three factors of engineered nanoparticles (ENPs) on plant systems will enhance our understanding of the benefits and risks of these tiny particles on the ecosystem balance. It will also provide appropriate guidelines for farmers to handle NPs in cropland with the utmost care and accuracy.